2020
DOI: 10.1136/bmjpo-2020-000736
|View full text |Cite
|
Sign up to set email alerts
|

Early neurodevelopmental outcomes of congenital gastrointestinal surgical conditions: a single-centre retrospective study

Abstract: BackgroundEvidence is emerging that surgery in the neonatal period is associated with increased risk of suboptimal neurodevelopmental outcomes (SNDO). The aim of this study was to describe neurodevelopmental outcomes (at 1 year) of neonatal surgery for congenital gastrointestinal surgical conditions (CGSC) and to explore risk factors.MethodsRetrospective study (2005–2014) of infants born ≥34 weeks gestation with CGSC and admitted to the surgical neonatal intensive care unit of Perth Children’s Hospital, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“… 36 A retrospective study using the GMDS-II at age 12 months ( n = 27) found normal neurodevelopment. 37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 36 A retrospective study using the GMDS-II at age 12 months ( n = 27) found normal neurodevelopment. 37 …”
Section: Resultsmentioning
confidence: 99%
“… 24 The study of Batta et al found that birthweight and length of stay in the hospital were associated with neurodevelopment at 1 year of age. 37 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the recent literature, our study found that neonates with CGISC develop postnatal growth restriction for weight and head circumference. 29 , 30 Studies in preterm infants have reported an association between postnatal growth restriction of the head circumference and adverse developmental outcomes. 31 33 Hence, it was reassuring that postnatal growth restriction for head circumference was less severe in the probiotic group in our RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one could hypothesise that probiotic supplemented group will have better neurodevelopmental outcomes. Our recent retrospective study 30 with a sample size of 400 found the incidence of suboptimal neurodevelopmental outcomes (SNDO) to be 16% in term and near-term neonates with CGISC. A sample size of 516 infants (258 in each arm) will be required to have 80% power at the two-sided 5% significance level to detect a 50% difference in the primary outcome (16% in controls and 8% in the probiotic group).…”
Section: Discussionmentioning
confidence: 99%